Letter from Oscar B. Nunez to Jane Tolmach - Oscar B. Nunez:::::: (1973)
A letter from Oscar Nunez, the general manager of Malibu Homes, inc., to Jane Tolmach congratulating her on her election to the position of Mayor of Oxnard.